Anaerobic digestion of corn straw pretreated by ultrasonic combined with aerobic hydrolysis. (December 2021) - Chu, Xiaodong; Cheng, Qiushuang; Xu, Yonghua; Luo, Lina; Wang, Ming; Zheng, Guoxiang; Zhang, Hongqiong; Yi, Weiming; Liu, Xiaofeng; Sun, Yongming; Sun, Yong
Highlights: An effective way was studied for corn straw fermentation experiment. The lag phase of fermentation can accelerate after ultrasonic pretreatment. The performance of AD and the yield of methane can improve by ultrasonic pretreatment. The highest cumulative methane production was 198.56 mL/g VS, 46.73% higher than untreated group. Abstract: Corn straw (CS) was pretreated by ultrasonic combined aerobic with biogas slurry as medium for anaerobic digestion (AD), that strengthened the degradation efficiency CS, varied in the composition of digestion slurry, thereby the methane production was increased. Central combinatorial design (CCD) test was used to treat CS at ultrasonic power (200, 400, and 600 W), time (10, 20, and 30 min) and AD for 25 days, at 37 ± 1℃. According to data showed that the pH and volatile fatty acids (VFAs) affected methane production directly. With an ultrasonic power 309 W, time 26 min, it reached the maximum content of VFAs with 16.24 g/L, the cumulative methane production achieved the highest with 198.56 mL/g VS, which was 46.73% higher than unpretreated raw material as CK. Ultrasonic-aerobic hydrolysis pretreatment can obtain higher VFAs and methane production content in a short period of time that is great significance to biogas engineering.